Effect of Different Polar Solvents and Stabilizer and Co-Stabilizer Concentration on Dispersion Polymerization of Styrene - Mohammad Reza Jozaghkar; Farshid Ziaee; Mohammad Reza Afkhami Aqda; Nakisa Yaghobi; Seyed Mehrdad Jalilian (علوم و تکنولوژی پلیمر, 2019)
Hypothesis: Dispersion polymerization has proven to be a useful technique for preparing uniform polymer particles in the micrometer size range. The polymer synthesized with this method can be utilized in various applications. The knowledge of the effect of process parameters on the droplets size and droplets size distribution is very important. As a result, this study was designed to investigate the effect of processing parameters on the droplets size and droplets size distribution of polystyrene (PS) microspheres synthesized by dispersion polymerization.Method: Dispersion polymerization was performed in a sealed glass tube at 65°C for 24 h. The effect of solvent type, stabilizer and co-stabilizer concentration on the droplets size and droplets size distribution of polystyrene microspheres was investigated by scanning electron microscopy (SEM) and Image J software. Also, the effect of a mixture of solvents and co-stabilizer concentration on the molecular weight and molecular weight distribution (PDI) of polystyrene was studied by gel permeation chromatography (GPC).Finding: The morphology results revealed that the aliphatic length of polar solvents affects the droplet size and droplet size distribution. At first, increase in the aliphatic length of polar solvent enhanced droplet size and droplet size distribution of polystyrene microspheres. Further increase in aliphatic length of polar solvent led to decrease in the droplet size and droplet size distribution. Addition of water to ethanol led to reduced droplets size compared to pure ethanol and enhancement in molecular weight and PDI. In addition to this, the presence of co-stabilizer did not change the droplet size and its distribution however, it increased molecular weight and PDI of polystyrene microspheres.